EFFECTIVENESS OF MODERN METHODS OF TREATING TYPE I MUCOPOLYSACCHARIDOSIS PATIENTS - L. S. Namazova-Baranova; N. D. Vashakmadze; M. A. Babaikina; E. N. Basargina; N. V. Zhurkova; A. K. Gevorkyan; L. M. Kuzenkova; T. V. Podkletnova; K. V. Zherdev; O. B. Chelpachenko; T. D. Degtyareva (Педиатрическая фармакология)
Type I mucopolysaccharidosis (MPS) is a hereditary metabolic disease related to lysosomal storage diseases. Alpha-L-iduronidase enzyme deficiency leads to dissimilar disease phenotypes and varying severity of symptoms. Researchers distinguish between three phenotypes of the disease: Hurler syndrome (mucopolysaccharidosis IH — severe form), Scheie syndrome (mucopolysaccharidosis IS — mild form), Hurler-Scheie syndrome (mucopolysaccharidosis I H/S — moderate form). The article presents a case of Hurler syndrome affecting cardiac, musculoskeletal and nervous systems, as well as data on case follow-up and treatment of a child at a modern multiprofile inpatient hospital. The article demonstrates that unlike the only previously possible palliative treatment, modern methods of treatment, such as enzyme replacement therapy, transplantation of bone marrow stem cells, umbilical cord blood or peripheral sources of stem cells and orthopedic correction, are effective.